Prevalence and healthcare seeking practice of work-related musculoskeletal disorders among informal sectors of hairdressers in Ethiopia, 2019: findings from a cross-sectional study - Tesfaye Hambisa Mekonnen; Getachew Guteta Kekeba; Jember Azanaw; Gebisa Guyasa Kabito (BMC, 2020)
Abstract Background Work-related musculoskeletal disorders (MSDs) are the major threats to public health, with a significant impact on workers, employers, and the general population. Musculoskeletal disorder related to work not only results in adverse health effects such as physical injury, disability, and a reduction in workers' quality of life, but it also places immense burdens on the use of healthcare facilities and a substantial loss of productivity. The purpose of this research was to discover the prevalence and associated factors of work-related MSDs among hairdressers in Oromia Special Zone Surrounding Finfine, Ethiopia. Methods A cross-sectional survey was carried out between March and April 2019. We included a total of 699 hairdressers with a systematic random sampling technique. Work-related MSDs was evaluated with the standardized Nordic Musculoskeletal survey, and the survey was administered by the interviewer. We employed SPSS version 20 software to perform a bivariate and multivariate analysis. A p-value of < 0.05 was considered a significant association. Results In total, 652 hairdressers were interviewed with a response rate of 93.2%. Participants' mean age was 33.19 (SD ± 9.639) years. The prevalence of work-related MSDs was 70.2% (N = 458) [95% CI (66.7, 73.9)] and 55.7% in the past 12-months and 7 days, respectively. The study showed the highest prevalence rate was observed in shoulder 53.7% (n = 350) followed by 53.4% (n = 348) neck and 53.2% (n = 347) low back. Of the participants, 33.4% (n = 153) perceived their pain to be severe whereas 28% (n = 128) a high disabling. Almost one-third (n = 187) of the respondents used healthcare services. Age [AOR = 2.73; 95% CI (2.55, 5.46)], work experience [AOR = 1.51; 95% CI (1.03, 2.20)], number of customers served per day [AOR = 2.35; 95% CI (1.35, 4.11)], and hours spent standing to make hair [AOR = 3.4; 95% CI (2.49, 7.77)] were significantly associated factors. Conclusion This study found work-related MSDs were prevalent among hairdressers, but the use of healthcare services remains low. Age, length of employment, number of customers served per day, and number of hours spent standing per day to make hair were significantly associated. Therefore, we recommend employers need to develop health and safety programs that account for factors related to the workplaces. The findings also demonstrate that health practitioners would encourage pain management procedures.